Group Cohesiveness Through Industrial Morale and Productivity - Singhal, Sandeep (Journal of Commerce and Trade, 2019)
A standard behavior can only be established along with a justified maintenance of mental health through group formation. Group formation in an organization and its cohesiveness place what impact on the group and the organization. This research throws the light on the working of the group. Here, in the study, the author seeps to investigate- (i) group cohesiveness as a factor of member morale, (ii) group formation can lead to less stress regarding work-related matters and (iii) group cohesiveness increases performance. The study was conducted in a manufacturing unit in Ghaziabad. This factory has a typical organizational structure with a supervisory hierarchy of workshops. Each workshop is made up of a group of skilled employees, who have in common a single supervisor and a work assignment in which individual taska are either similar or complementary. We come to a conception of group cohesiveness as a facilitating factor which determines the amount of Influence a group has but not necessarily the direction or the goal towards which the group influences operate. We see the variable, group cohesiveness, as being of sufficient importance to make its effects measurable. They are measurable even in a complex setting in which the formal social structure is designed to ignore or even suppress group effects and in which there are strong factors, such as in-dividual mobility, multiply group membership, out-plant associations, problems of reliable measurement and others, which tend to obscure primary group effects. Classification-JEL : D80, G30